الكليات الفقهية من خلال قوانين الفقهية لابن جزي - حميدة العدودي; خولة بن موفق; د/زيغمي نعيمي (جامعة عمار ثليجي الاغواط, 2023)
ملخص : لمنا بدراسة كل اٌت ابن جزي من خلال كتابه الموان نٌ الفمه ةٌ باب الب وٌع أنموذجاا . تضمنت الدراسة التعر فٌ بابن جزي الغرناط من ذكر نسبه وولاته ووفاته وش وٌخه وكذلن دراسة كتابه الموان نٌ الفمه ةٌ ومنهجه ح ثٌ جمع الفروع والمسائل على مذهب الإمام مالن . ثم عرفنا الكل ةٌ وب نٌا الفروق ب نٌها وب نٌ مشابهاتها، كل من المواعد والضوابط الفمه ةٌ . وذكرنا مصادر الكل اٌت وذلن من خلال النصوص الشرع ةٌ الكتاب والسنة وكذلن ألوال المأثور عن الصحابة والتابع نٌ وأئمة المذاهب الفمه ةٌ مع ب اٌن مكانتها وأهم تٌها . ثم خصصنا الجزء الأخ رٌ لدراسة الكل اٌت الفمه ةٌ ف باب الب وٌع وذلن من خلال ب اٌن ماه ةٌ الب وٌع ومشروع تٌه وأنواعه وأركانه مع عرض وتصن فٌ الكل اٌت المتعلمة بها مع التفص لٌ ف هٌا وذكر مماصدها . ح ثٌ توسع ابن جزي ف هذا الباب، أما الخاتمة فمد شملت أهم نتائج البحث . Summary: We have conducted a comprehensive study of Ibn Juzayy's juristic colleges through his book "Al-Qawanin al-Fiqhiyyah" (Jurisprudential Laws), focusing on the chapter of sales as a model . The study included an introduction to Ibn Juzayy al-Gharnati, his lineage,birth, death, and his teachers. It also examined his book on jurisprudential laws and his methodology, where he collected branches and issues based on the Imam Malik's school of thought. We then defined the colleges and highlighted the differences and similarities between them, including the juristic rules and regulations. We mentioned the sources of these colleges, which are derived from the textual sources of the Quran and Sunnah, as well as the sayings of the Companions, the Successors, and the juristic scholars, while explaining their significance and importance. The last part was dedicated to the study of juristic colleges in the chapter of sales, elucidating the nature, legitimacy, types, and pillars of sales, along with the presentation and classification of related colleges, providing detailed explanations and mentioning their objectives. Ibn Juzayy extensively covered this chapter. Finally, the conclusion encompassed the most important research findings